Preventive Detention with Emphasis on Article150 of the Islamic Penal Code of Iran 1392 - Ali Hossein Nadjafi Abrandabadi; Soodabeh Rezvani (Faṣlnāmah-i Pizhūhish-i Huqūq-i Kiyfarī, 2015)
Preventive detention of mental disorders applies for ensuring public protection and for preventing potentially dangerous offenders from reoffending. Former Article 48 and Article 150 of Islamic penal code 1392 are the most important examples of the preventive approach in Iran's law. In fact, preventive detention is a sort of pre-emptive action for public protection. In this measure, criminal law is moving from a retributive approach to a forward-looking approach and applied to pre-crime. Therefore, the article, examines this approach with emphasis on Article 150 of the Islamic Penal Code of Iran and the United States of America’s and France's law that are examples of punitive penal policy.